Implementation Of Technique For Order Preference By Similarity To Ideal Solution Method In Performance Assessment Of Best Medical Personnel In Public Hospitals Kepahiang Area - Ragil Fadilla Rahma Dani; Liza Yulianti; Lena Elfianty (Penerbit Jurnal Indonesia, 2024)
In assessing the performance of the best medical personnel at the Kepahiang Regional General Hospital, there are several criteria that are used as an assessment. This assessment is based on the assessment of the performance of medical personnel, namely Service Orientation, Responsibility, Discipline, and Attendance. In this study, the technique for order preference by similarity to ideal solution (TOPSIS) method is applied with a decision support system, each of the criteria in the assessment of the performance of medical personnel is compared with one another, thus providing an output of priority intensity values for each medical personnel. From the description above, it can be concluded that in assessing the performance of the best medical personnel, only those who meet the criteria with the highest value will be selected.